Liquidity management under non-interest (Islamic) banking - Central Bank of Nigeria; Monetary Policy Department, Central Bank of Nigeria (Abuja : Central Bank of Nigeria, 2012)
Discusses the liquidity management process in an environment of non-interest or (Islamic) banking
Includes bibliographical references.
oif 16/11/16
Ref.
Keywords: Monetary policy; Banks and banking; Liquidity management